Intellectual and Academic Outcome Following Two Chemotherapy Regimens and Radiotherapy for Average-Risk Medulloblastoma: COG A9961 - Ris, M. Douglas (Pediatr Blood Cancer, 2013)
PURPOSE. Assess the intellectual and academic outcomes as well as risk factors associated with treatment for average-risk medulloblastoma in childhood using 23.4 Gy of craniospinal radiotherapy plus adjuvant chemotherapy. METHODS. From an overall sample of 379 enrolled in the parent study (COG A9961), 110 patients received a total of 192 assessments over more than 5 years with standardized IQ and academic achievement tests. Random coefficient models of the various outcomes were developed that incorporated covariates including chemotherapy regimen, age at diagnosis, sex, initial Full Scale IQ, and mutism. RESULTS. Participants in this study were found to be comparable to the overall sample in all demographic, disease, and treatment factors, except there were more gross total resections in the subsample undergoing intellectual and academic assessment. Major findings include significant decline in both intellectual and academic domains over time that were greater in children who were younger at diagnosis and had higher initial intelligence test scores. Children with mutism were at higher risk for initial effects on intelligence. No effects of sex were found. CONCLUSION. These results show progressive decline over several years post-treatment in standardized intellectual and academic scores. Despite recent improvements in therapies for these children, most notably a decrease dose of craniospinal radiation, they remain at risk. The pursuit of less toxic treatments, particularly for younger children, should continue. Neuropsychological surveillance should be routine at centers treating children with brain tumors. Pediatr Blood Cancer 2013;60:1350–1357.